Perspektif Pedagang Kuliner di Kawasan Wisata Geosite Sipinsur Tentang Manfaat Mengikuti Ibadah Minggu - Debora Rosa Maria Pardosi; Elisamark Sitopu; Meditatio Situmorang; Bernhardt Siburian; Bestian Simangunsong (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The aim of this research is to describe the perspective of culinary traders in the Sipinsur tourist area regarding the benefits of attending Sunday worship. Sunday worship is our response to the work of salvation that God has given us and as a sign of thanksgiving and respect which is carried out by praising and glorifying His name. This shows how important it is to worship together with fellow believers as a form of gratitude for God's work in each person's life. The benefits of worship are also much greater because they contain promises, both for this life and the life to come. The consequences of a life of worship are blessings that can already be felt (Rom.14:17) because the kingdom of God is not about eating and drinking but about righteousness and happiness by the holy spirit. This study used descriptive qualitative method. Data was collected through in-depth interviews with 8 traders who actively trade in the Sipinsur Geosite tourist area. Data analysis was carried out by identifying thematic patterns and interpreting the meaning of traders' answers. The results of this research show that the majority of culinary traders in the Sipinsur Geosite tourist area have not felt and do not even understand the benefits of attending Sunday worship in their lives. So this is what causes the culinary traders to be absent from Sunday services. Therefore, in this article the author provides an explanation to church ministers to provide a better understanding regarding the meaning and benefits of Sunday worship.